Strength, Sorption and Chemical Properties of Ceiba Pentandra and Tectona Grandis Wood Composite - Adefisan, O. O.; Oyelola, D. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The enormous quantities of wood wastes in Nigerian sawmills and disused polystyrene from packaging can be converted to value added composite products thus curtailing their indiscriminate disposal; enhancing greener environment. This work examined the strength, sorption and chemical properties of wood composites made from Ceiba pentandra and Tectona grandis. Ceiba pentandra (Araba) and Tectona grandis (Teak) composite boards were made from polystyrene glue and a conventional water-based adhesive used in the wood industries. The fabricated boards were tested for strength and sorption properties while the functional groups of the composites were determined using the Fourier Transformed Infrared Radioscopy technique. The results obtained revealed that the composites had low strength, poor sorption properties and can only be utilized as insulating components in building construction. Polystyrene based composites possessed higher strength (Modulus of Rupture: 2.2 – 4.9 N/mm2) and enhanced sorption properties (Water Absorption: 14.2 - 98.5 %; Thickness Swelling: 0.61 - 3.45%) in comparison with those of the water-based adhesives (Modulus of Rupture: 1.6 – 2.8 N/mm2; Water Absorption: 33.4 – 158.4 % and Thickness Swelling: 1.80 – 7.41%) possibly due to preponderance of aromatic compounds which enhanced interfacial bonding. Increase in glue content significantly enhanced the strength and sorption properties of the wood composites